1, 6-O, O-Diacetylbritannilactone suppresses activation of mast cell and airway hyper-responsiveness. (4th July 2017) - Jin, Meihua; Kim, Sungun; Qin, Nan; Chen, Xi; Ji, Ning; Tang, Sheng-an; Kong, Dexin; Lee, Eunkyung; Duan, Hongquan
Abstract: Mast cells play critical roles in allergic disorders such as atopic dermatitis and allergic asthma. The aim of this study was to investigate the anti-inflammatory and anti-asthmatic activities of 1, 6- O, O -diacetylbritannilactone (OODBL) isolated from Inula japonica Thunb. ( I. japonica ) in a murine asthma model and bone marrow-derived mast cells (BMMCs). In an ovalbumin-induced asthma model, OODBL administration attenuated the airway hyper-responsiveness induced by aerosolized methacholine and serum IgE level in asthmatic mice. In vitro system, we found that OODBL reduced leukotriene C4 production and degranulation through the suppression of cytosolic phospholipase A2 phosphorylation and phospholipase Cγ-mediated Ca 2+ influx in IgE/antigen-stimulated BMMCs. Taken together, OODBL may have therapeutic potential in the treatment of allergic diseases such as asthma.